Bahasa Kopi di Instagram: Kajian Sosiolinguistik Register melalui Hashtag - Yulia Tutik Nurfia; Suyanti Suyanti (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
This study examines the phenomenon of coffee language on Instagram, focusing on the linguistic registers that emerge through the use of hashtags. Using a sociolinguistic perspective, this research explores how coffee-related language functions as a means of constructing social identity, negotiating community membership, and expressing self-representation among Instagram users. The study employs a descriptive qualitative approach, with data collected through content analysis of Instagram posts related to coffee culture, particularly those utilizing popular coffee-themed hashtags.The findings reveal that hashtags serve not only as tools for categorizing content but also as markers of register that communicate cultural values, taste preferences, lifestyle orientations, and the social identities of coffee enthusiasts. Hashtags strengthen community solidarity, facilitate interaction among members, and create a discursive space where users can craft and maintain their digital personas. Moreover, the results indicate that coffee language on Instagram operates as a dynamic cultural communication practice, in which users employ technical terms, sensory metaphors, and specific linguistic variations to signal expertise, community closeness, or aesthetic expression.This study contributes significantly to a deeper understanding of digital language dynamics, register practices, and cultural identity formation on social media, particularly within the growing global coffee community.